Seniors celebrate with President Lawrence Bacow at Gifford House at the Senior Class Reception. Photo 212 - Ko, Melody (Tufts Archival Research Center, 2008)
Seniors celebrate with President Lawrence Bacow at Gifford House at the Senior Class Reception.